Theory and practice in mathematics teacher education : building a learning community - Guðbjörg Pálsdóttir; Guðný Helga Gunnarsdóttir; Jónína Vala Kristinsdóttir (2008)
Fyrirlestur haldinn á „Den 10. nordiske læreruddannelseskongres” sem haldin var í Kennaraháskóla Íslands 21.-24. maí 2008 In Iceland education of compulsory school teachers has been at Bachelor of Education level since 1971. Iceland University of Education1 has been the main institution educating teachers for compulsory schools and has been graduating 200-250 compulsory school teachers with a B. Ed. degree yearly for the last 10-15 years. The teacher education has been under constant development and students have been able to specialize in mathematics teaching and learning to a different degree. The most recent reforms open more possibilities for specialization both within educational studies and certain professional areas or subjects. Specialization in mathematics and mathematics education is currently 80 ECTS out of 180 ECTS. The latest reforms also allow students to commence graduate studies directly after finishing undergraduate degrees.